1978
DOI: 10.1139/z78-230
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the external form and skeleton of the calcareous sponges Clathrina coriacea and Clathrina blanca from Santa Catalina Island, California

Abstract: The external morphology and skeleton of Clathrina coriacea (Montagu) and Clathrina blanca (Miklucho-Maclay) from Santa Catalina Island, California, were studied to determine whether the differences, taken as a whole, were consistent and justified the separation into two distinct species. Clathrina coriacea is an encrusting sponge, whereas C. blanca is pedunculate in form. The diameter of the uncontracted anastomosing tubes is significantly greater in C. coriacea. The skeleton of the two sponges consists of equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 5 publications
1
22
1
Order By: Relevance
“…Seasonal patterns are common in temperate habitats (Elvin 1976; Osman 1977; Sutherland & Karlson 1977; Sebens 1986). For sponges, seasonal cycles with higher growth rates in winter–early spring (the reverse of what we have found) have been reported by Johnson (1979). In contrast, Ayling (1983) found fluctuations in sponge sizes not related to seasonal or reproductive cycles, and no seasonal pattern of growth has been observed in other Mediterranean species (Pansini & Pronzato 1990).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Seasonal patterns are common in temperate habitats (Elvin 1976; Osman 1977; Sutherland & Karlson 1977; Sebens 1986). For sponges, seasonal cycles with higher growth rates in winter–early spring (the reverse of what we have found) have been reported by Johnson (1979). In contrast, Ayling (1983) found fluctuations in sponge sizes not related to seasonal or reproductive cycles, and no seasonal pattern of growth has been observed in other Mediterranean species (Pansini & Pronzato 1990).…”
Section: Discussionsupporting
confidence: 81%
“…The 2‐year monitoring revealed that the growth rate of small specimens of C. crambe was extremely low, especially if compared with that reported for massive demosponges (Dayton 1979) or calcareous sponges (Johnson 1979). Sizes increased on average about 2·5 times in 26 months (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Johnson (1979) found for CIathrina coriacea and C. blanca that most vigorous growth of these species occurred at lower habitat temperatures. Similar results have been found for a number of other species (Coe 1932, Coe & Allan 1937, Wells et al 1964.…”
Section: Discussionmentioning
confidence: 83%
“…True diactinal spicules with two rays in different Note that the rays are not in the same plane (SEM) (x600) (Johnson, 1978a). (Courtesy Dr. M. Fischel Johnson.…”
Section: Calcareous Deposits: Morphology Chemistry Distributionmentioning
confidence: 99%